Pengaruh Inovasi Produk, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pizza Hits Studi Kasus Konsumen Pizza Hits Kecamatan Dau Kabupaten Malang - Junaidi, Junaidi; Widarko, Agus; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Item development may be a vital figure in supporting the victory of the company itself, both benefit suppliers and fabricating companies. Within the current period of modernization, companies are confronted with competition. Competition requests drive companies to take after shopper requests and advertise changes. This inquire about points to know the affect of item advancements, qualities, and costs on shopper requests of Pizza Hits. As one of the objects of current inquire about, specifically with respect to culinary or handled flour, there are numerous advancements, as one illustration of prepared flour development within the city of Malang is Pizza Cottage, Pizza Ndezo, Domino's Pizza and numerous others, but at Pizza Hits as an outlet that serves different sorts of pizza flavors such as corn pizza, chocolate pizza, and numerous other variations. Each buyer has distinctive characteristics, this has been clarified in buyer behavior. Agreeing to Kotler (2018 :166) customer behavior is the consider of how people, bunches and organizations select, purchase, utilize and how products and administrations, thoughts or encounters fulfill their needs and wants. Keywords: Item Advancement, Item Qualties and Costs, Shopper Behaviors